Proteksi Keamanan Data dengan Menerapkan Algoritma Bacon Cipher dan ROT128 - Rahmatsyah, Indra; Siregar, Yunita Sari; Khairunnisa, Khairunnisa (Explorer, 2024)
The data storage and information exchange activities digitally have risks and of course must be accompanied by information security. Various ways are done to protect data such as hiding data with steganography techniques or by encoding data with cryptographic techniques. If in general the steganography technique is done by inserting data into image, audio or video media, but in this study the data will be inserted or hidden into a text file as a media (cover message) to hide the data. While data security with cryptographic techniques is done by changing the data to be kept secret (plaintext) into encoded data (ciphertext) so that the data cannot be understood by people who do not have legality in the data. Therefore, with this method of securing research files, it produces a test of blackbox testing of encryption and description and extraction. Where is the result of the encryption on the encrypted text file using the ROT128 algorithm with a time of 1.82ms and where is the result of the description on the text file producing a decrypted text file using the ROT128 algorithm with a time of 1.47ms. After carrying out the extraction process on the resulting text file description using the Bacon Cipher algorithm, it will produce the original text with a time of 13.95ms